Sociocultural Aspects of Transgender Slang - Surana, Surana (IJOLTL (Indonesian Journal of Language Teaching and Linguistics), 2021)
This study examines the sociocultural aspects of waria’s slang. Considering the current problems, the descriptive method was used to describe the results of this study. The object of this study is the various language used by transgenders in their daily communication. The data were collected, categorized, analyzed, and the results were presented in the form of a description along with examples. Sociocultural aspects that exist in waria’s slang can be the sociological, sociolinguistics, as well as cultural aspects of the slang emergence among transgenders. Sociological aspects include the use of slang among transgenders inclusively. Those aspects are the use of speech units in the form of words, phrases, sentences, and discourses. Furthermore, the establishments of waria’s slang are as follows: the sounds game, permutation, a play, replacements, additions, acronyms, and analogies. While the cultural aspects include waria’s slang function within the culture among the society members, which for: humoring, bullying, unifying, and as a communication tool.